المصطلح السردي، تعريباً وترجمة، في النقد الأدبي العربي الحديث - أبو هيف عبد الله (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
عالج البحث تاريخية المصطلح النقدي وتطوره في مدى علمية النقد الأدبي كلما ارتبط بالمعرفية والمنهجية والاصطلاحية. وأضاء عناصر المصطلح النقدي وتحققها ولاسيما التواصل الحضاري والمعرفي وتمثل الهوية باستمرار التقاليد الأدبية وعناصر التمثيل الثقافي الأخرى. وتأمل البحث في واقع المصطلح النقدي بحالتيه النظرية والتطبيقية قياساً إلى المنظورات الفكرية وسبل منهجيتها. وأبان البحث تطور المصطلح السردي ضمن جهود النقاد والباحثين العرب خلال العقدين الأخيرين والانتقال من الإخبار والقصّ وأشكال النثر القصصي المتعددة في التراثين العربي والغربي إلى السرد وعلمه بتأثير المناهج النقدية الحديثة، وكان التطور الأبرز مع هذا العلم قيامه على الشكلانية الروسية والبنيوية وورثتها، ولاسيما العلامية (السيميولوجيا)، ونظر البحث في تعريب المصطلح السردي وترجمته وفق المنهج العلامي (السيميائي)، في جهود المترجمين منذر عياشي (كتاب «علم الإشارة ـ السيميولوجيا» لبيير جيرو)، وسعيد الغانمي (السيمياء والتأويل لروبرت شولز)، وعبد الرحمن أبو علي (السيميائيات أو نظرية العلامات لجيرار دولودال)، ورشيد بن مالك (كتاب «السيميائية وأصولها وقواعدها» لجان كلود جيرو ولوي باتييه، وكتاب «السيميائية مدرسة باريس» لجان كلود كوكي)، ونجيب غزاوي (كتاب «في المعنى ـ دراسات سيميائية» لالجير داس جوليان جريماس)، وشاكر عبد الحميد (كتاب «معجم المصطلحات الأساسية في علم العلامات السيموطيقا» لدانيال تشاندلر)، والسيد إمام وعابد خزندار (ترجمتهما لكتاب جيرالدبرنس «المصطلح السردي: معجم مصطلحات»). وتناول البحث آفاق المصطلح السردي في التعريب والترجمة من خلال خلاصات حول الممارسة النقدية في الترجمة والتأليف. The research discusses the history of the critical idiom: its development and connection with knowledge and methodology. The research sheds light on the aspects of the literary criticism with respect to identity, literary traditions, and cultural exchange. It also examines the position of the critical idiom in its practical and theoretical sides. The research also shows the development of the narrative idiom through the last two decades and the transition from telling and narrating, especially how the various forms of the fictional prose in both the Arabic and Western cultures are influenced by the modern critical schools like Russian formalism and Structuralism. The research discussed Arabzing the narrative idiom and translating it according to the semiotic methodology in the efforts of Monzer Ayashi in his Science of Sign Symiology by Pierre Jiro, Saed al – Ghanimi in Symiology and Interpretation by Robert Schwitz, abd al – Rahman Abu Ali in Symiology or the Signs’ theory by Girard de Ie Dal, Rashid Ben Malek in Symiology and its Origins and Rules by Jean Claud Jiro and Louis Patieh, and the in Symiology, the School of Paris’ by Jean Claud Kooky, Najib Ghazawi in On the Meaning - Symiotic Studies" by Lalger Das Julian Grimas, Shaker Abd al - Hamid in Dictionary of Basic Idioms in the Science ofSimiotica Signs by Daniel Chandler, al- Sayed Imam and Abed Khaznadar in their translation of a book by Gerald Prince The Narrative idiom an idiomatic dictionary. The research discusses the horizons of the narrative idiom in Arabization and translation through summaries about the critical practices in translation and composition.